IMPLEMENTATION OF AGILE PERFORMANCE MANAGEMENT IN THE DIGITAL ERA IN GLOBAL COMPANIES AND STARTUPS IN INDONESIA - Dewi, Irma Nurmala; Khaeruman, Khaeruman; Ahmed, Abdal (Yayasan Education and Social Center, 2024)
This study aims to analyze the implementation of agile performance management in global companies and startups in Indonesia in the digital era. The primary objective of this investigation is to determine the effects of agile methodology implementation on operational efficiency, employee satisfaction, flexibility, responsiveness, and responsiveness. Additionally, it will evaluate the obstacles encountered during the implementation process. The results of the study indicate that the implementation of agile increases the company's responsiveness to customer needs, with startups such as ABC Tech experiencing an increase of up to 30%. In addition, global companies such as PT. XYZ recorded an increase in operational efficiency of 20%. Implementing agile methodologies enhances employee satisfaction due to a more collaborative and transparent work environment. Factors that facilitate the successful implementation of agile methods encompass an innovative organizational culture, technological support, and sufficient human resource competencies. However, significant challenges include resistance to change and resource constraints, especially among senior employees. Based on the findings of this study, the success of agile implementation is highly dependent on the implementation of adaptive leadership and the support of organizational culture. Companies interested in implementing agile performance management to improve resource performance in the digital era can benefit from the insights provided by these findings